Legal Status and Inheritance Rights of Wives and Children from Unregistered Polygamous Marriages: A Socio-Legal Study at the Religious Court - Rani Rahayu; Mairul Mairul (SEAN Institute, 2026)
Marriage registration is a legal requirement in Indonesia to ensure legal certainty and the protection of civil rights, including inheritance rights. However, unregistered polygamous marriages continue to occur, resulting in legal uncertainty, particularly for wives and children. This study aims to examine the legal status and inheritance rights of wives and children from unregistered polygamous marriages and to analyze judicial considerations in resolving such cases at the Religious Court. This research employs an empirical legal (socio-legal) approach with a conceptual and juridical-empirical perspective. Data were obtained from secondary legal materials and semi-structured interviews with a Senior Judge at the Religious Court of Bukittinggi conducted on January 26, 2026. The data were analyzed qualitatively through data editing, thematic classification, and interpretative analysis. The findings indicate that marriage registration is the primary factor determining inheritance rights. Wives from unregistered marriages have weaker legal standing due to the absence of formal legal recognition. In contrast, children receive stronger legal protection through lineage recognition and legal mechanisms such as wasiat wajibah. Judges play an important role in ensuring justice by applying both formal legal provisions and substantive justice principles based on Islamic law and child protection. This reflects the Religious Court’s function in balancing legal certainty and justice.